Fracture criteria and surrogate models for bearing strength of mechanically fastened joints on hybrid composite laminates - Wallner, Cassio; Almeida, Sergio Frascino Muller de [UNESP] (SAGE Publications, 2024)
In this work two novel criteria for strength predictions of bearing failure on mechanically fastened composite joints are proposed for preliminary design. These criteria can estimate the bearing strength of hybrid laminates, which makes them innovative and applicable to a much wider range of aircraft structures that usually use this type of laminate in mechanical joints. The new approach uses characteristic lengths d0 and a0 to estimate the joint strength in bearing. Three surrogate models based on a linear regression of lamination parameters and AML (Angle Minus Load) parameter are proposed to provide accurate estimates for characteristic lengths d0 and a0 for a given set of these parameters. The regression models used three or two lamination parameters or a single parameter AML. They were applied to experimental results of six different laminate families including three hybrid laminates. The modified average bearing stress criterion (ABSC) outperformed the modified point bearing stress criterion (PBSC) in all cases. The results of the ABSC have a maximum discrepancy for the bearing strength of all laminate families of 2.77% and 1.91%, for the three and two parameters, respectively. The single parameter regression model using AML had a maximum discrepancy of 8.83%. All these results compare very favorably with the criteria proposed in the literature, including the AML regression that had the worst accuracy. Therefore, these criteria together with the proposed surrogate models can be used to minimize the number of tests required for the aircraft development, being a good candidate for preliminary design.
Keywords: bearing strength; composite mechanical joint; fracture criterion; lamination parameters; surrogate model